Dual targeting of tumoral cells and immune microenvironment by blocking the IL-33/IL1RL1 pathway - Denggang Fu; Hua Jiang; Alan Long; Ella Harris; Hongfen Guo; Maegan L. Capitano; John Wrangle; Joshua R. Faust; Anilkumar Gopalakrishnapillai; Santhosh Kumar Pasupuleti; Baskar Ramdas; Reuben Kapur; et al. (Nature Communications)
Abstract Leukemia stem cells (LSCs) are a small yet powerful subset of leukemic cells that possess the ability to self-renew and have a long-term tumorigenic capacity, playing a crucial role in both leukemia development and therapy resistance. These LSCs are influenced by external and internal factors within the bone marrow niche. By delving into the intricate interplay between LSCs and their immune environment, we can pave the way for innovative immunotherapies that target both the malignant stem cells and the suppressive immune microenvironment, addressing both the “seed” and the “soil” simultaneously. Through the analysis of public datasets and patient samples, we show that elevated IL1RL1 expression correlates with poor prognosis and therapy resistance in acute myeloid leukemia (AML). At the core of this process, stem cell leukemogenesis initiation and maintenance signals are driven by a stress-induced IL-33/IL1RL1 autocrine loop. This LSC-induced IL-33/IL1RL1 signaling fosters an immune regulatory microenvironment. Therefore, IL1RL1 emerges as a promising therapeutic target, with IL1RL1-specific T cell-engaging bispecific antibodies holding great potential as cutting-edge immunotherapeutics for AML.